Poecilimon zonatus Bolívar (ORTHOPTERA, TETTIGONIIDAE) REVISITED: GENETIC DATA REVEALED TWO NEW SPECIES AND ONE NEW SUBSPECIES - Sarp Kaya (Trakya University Journal of Natural Sciences, 2018)
Poecilimon Fischer (Orthoptera, Tettigoniidae) is the most species-rich genus of the respective order and family in Anatolia. However, intrageneric diversity still needs to be documented. Poecilimon zonatus Bolívar is a species with a relatively wide range of distribution in Anatolia compared to other congeners. The present study aims to examine the diversity of P. zonatus using an integrated approach. The diversity of the species was documented using data based on DNA sequences, male calling song and morphology. Automatic species delimitation tests applied to genetic data revealed a cryptic diversity in P. zonatus complex and suggested two new species and one new subspecies. The song data supported the new species, but morphology remained less productive in this respect. The new taxa defined in the light of the obtained data are; Poecilimon isozonatus sp. n., Poecilimon ciplaki sp. n. as Poecilimon ciplaki ciplaki subsp. n. and Poecilimon ciplaki denizliensis subsp. n. These taxa together with P. zonatus were considered a species complex within P. zonatus group. The phylogenetic tree produced from nad2 gene sequences supported the following relationships of P. tauricola + (P. ciplaki + (P. zonatus +P. isozonatus)) relationship.